Stress Simulation of Chassis Crossover Electric Vehicle - Tito Shantika; Tarsisius Kristyadi; Hendra Hendra (JURNAL KAJIAN TEKNIK MESIN, 2020)
The development of an electric vehicle chassis is one step in the design process of a vehicle, especially for crossover vehicles that are being designed. The chassis design of the vehicle must have a chassis that is solid and can sustain all the loads that occur on the chassis, such as passenger loads, electric motors and so on. In the chassis design process, stress analysis is needed to verify the strength of the chassis if the loads that are applied. Stress analysis begins with making an initial model of an existing chassis using CAD then stress analysis using FEA Solidworks software. Stress analysis includes static and crash load. The results of the analysis under static load conditions obtained a maximum stress that occurs at 206 MPa, a factor of safety = 1.69, and a deflection of 0.4 mm where the chassis deflection due to bending is less than 1 mm. Keywords: chassis, EV, strength simulation, FEA.